Kharakteristika frustriruyushchego sostoyaniya u lyzhnikov-gonshchikov posle uchebno-trenirovochnoi i sorevnovatel'noi deyatel'nosti - Sivakov, V. I.; Makarenko, V. G. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The purpose of this research was to determine the influence of the frustrating condition to the humanisation processes and sports skill of speed skiers after the educating-training and competitive activity. The estimation of the adequacy and not adequacy of the physical loads was determined on the cardiac rate, the mood, the weariness and Rozensweig's test in 1 hour after educating-training occupations. The successful and unsuccessful competitive activity came to light on V.L. Marischuk's technique, the protocol of competitions and self-estimation of speed skiers also. 18 speed skiers have taken part in the research. The research brings to light, that the unsuccessful performance in competitions promotes the increase of the uneasiness, the aggression, and to decrease the self-estimation, the peaceful disposition, the restraint also, that confirms the mental intensity at skiers in the frustrating situation. The orientation and type of the frustrating reaction and its optimisation at speed skiers in the educating-training and competitive activity is determined. The psycho-pedagogical control of the frustrating condition will allow to open the additional non-realised resources to increase the sports skill of speed skiers.